School Readiness Analysis in Student Profile Reinforcement Project of Pancasila and Rahmatan Lil Alamin (P5-PPRA): Implement Simulation At MAS Daruzzahidin - Indra Indra; Amna Emda (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
The Reinforcement Project Profile of Pancasila and Rahmatan Lil Alamin for Student activity (P5-PPRA) is a strategic effort to shape students' character in accordance with Pancasila values. The success of the implementation of P5-PPRA is highly dependent on the readiness of the school as the spearhead in the learning process. This study aims to analyze schools' readiness to implement P5-PPRA at the Daruzzahidin Private Islamic High School (MAS). This study uses a qualitative approach with a descriptive research design. Data collection was carried out through direct observation of the P5-PPRA preparation activities and in-depth interviews with teachers. Data analysis used the Miles and Huberman model. The study results showed that teachers at MAS Daruzzahidin had made initial preparations in designing the P5-PPRA activities that will be implemented in 2024. However, several aspects still need to be improved, such as mastery of teaching materials related to P5-PPRA, development of innovative teaching materials, and more intensive collaboration between teachers. Based on the results of the study, it can be concluded that the school's readiness in implementing P5-PPRA at MAS Daruzzahidin is still in its early stages. There needs to be a more intensive effort to improve teacher competence in designing, implementing, and evaluating P5-PPRA activities. Thus, students can gain meaningful learning experiences and are able to implement Pancasila values in everyday life